Safety and feasibility of electrochemotherapy in patients with unresectable colorectal liver metastases: A pilot study. (August 2017) - Coletti, Laura; Battaglia, Valentina; De Simone, Paolo; Turturici, Laura; Bartolozzi, Carlo; Filipponi, Franco
Abstract: Background and objectives: Electrochemotherapy is a novel ablation technique combining chemotherapeutic agents with reversible cell membrane electroporation. Previous experiences have shown its efficacy for cutaneous tumors. Its application for deep-seated malignancies is under investigation. We performed a prospective, pilot study to evaluate the feasibility, safety, and efficacy of intraoperative electrochemotherapy for otherwise unresectable colorectal liver metastases. Methods: Electrochemotherapy with bleomycin was combined with open liver resection and performed with linear or hexagonal needle electrodes according to an individualized pretreatment plan. The primary endpoints were: feasibility, as ratio of completed to planned treatments; safety, and efficacy, as per response assessed at 30 days with MRI and according to RECIST. The secondary endpoint was overall and progression-free survival at month 6. Results: A total of 9 colorectal liver metastases were treated in 5 patients with 20 electrode applications. No intraoperative complications were observed. At day 30, complete response was 55.5% and stable disease 45.5%. All (5) patients reached a 6 months overall survival, and 4 out of 5 patients had 6 months progression free survival. Conclusions: Electrochemotherapy is a feasible and safe adjunct to open surgery for treatment of unresectable colorectal liver metastases. Larger studies and longer follow-ups are favored to better define its role in the treatment of secondary liver malignancies. Highlights: Electrochemotherapy is a novel ablation technique combining chemotherapeutic agents with reversible cell membrane electroporation. Its application for deep-seated malignancies is under investigation. We present the results of a prospective, pilot study to evaluate the feasibility, safety, and efficacy of intraoperative electrochemotherapy combined with open liver surgery for otherwise unresectable colorectal liver metastases. A total of 9 colorectal liver metastases were treated in 5 patients with 20 electrode applications. No intraoperative complications were observed. At day 30, complete response was 55.5% and stable disease 45.5%. The 6-month overall and progression-free survival was 100% and 80%, respectively. Larger studies and longer follow-ups are favored to better define its role in the treatment of secondary liver malignancies.